UPAYA PENINGKATAN PRODUKTIVITAS TERKAIT MOTIVASI DAN DISIPLIN KERJA KARYAWAN PT. KARINDO PERSADA - Intan Ummu Asriani; Tyna Yunita (Universitas Nasional, 2019)
PT. Karindo Persada is a general contracting company in the service and production of aluminum and composite panels that is growing rapidly in Bekasi. Delays in the delivery of goods and work systems implemented by the company where employees are fully responsible for the delivery of goods if there is damage to goods in the shipping process. This is allegedly due to lack of employee welfare and lack of employee work discipline very influential on the survival of the company. After analyzing using the IFAS (Internal Factor Analysis System) and EFAS (External Factor Analysis System) matrix, it is known that the company's internal strategic factors which consist of strengths and weaknesses show a weighted score of 2.09. and the company's external strategic factors consisting of opportunities and threats show a weighted score of 2.38. The results of the study of factors that hinder or challenges in increasing employee work productivity: initial selection and training. Knowledge training is needed for employees to increase their motivation and work discipline, this is done to increase employee knowledge so that even though the education level of employees is weak, employees get knowledge from the company. The knowledge provided can be directed in accordance with the objectives to be achieved by the company. This will have an impact on increasing productivity.